Crise econômica americana dos anos 2000: análise a partir de Minsky - Diogo, Elton Vianney (2012)
The objective of this paper is to present an interpretation of the U.S. financial crisis started in 2007, analyzing the structures and processes mortgages indebtedness of U.S. households, according to the theoretical framework suggested by Hyman Minsky, using his studies Financial Instability . Featuring two important elements in the process of crisis. The first has to do with the fact that crises behave in cycles, beginning in a boom phase where the macroeconomic environment is favorable, until some exogenous event changes the scenario and the agents indebted, become insolvent. From there, in search of money to cope with shortages monetary, will liquidate its assets at ever lower prices and thus enters into the stage of collapse. The second element is related to excessive financial liberalization, ie a problem of the very structure of the financial system that has a character loosely regulated, especially with the advent of financial innovations, would contribute to weakening the whole system. The paper seeks to show, therefore, that the economic instability that occurred in the American crisis of 2007 has to do with the fragility of the financial system, as Minsky shows in their theories.